How to Modulate Peripheral and Central Nervous System to Treat Acute Postoperative Pain and Prevent Pain Persistence - Cazzaniga, Sara; Real, Giovanni; Finazzi, Simone; Lorini, Luca F.; Forget, Patrice; Bugada, Dario (Current Neuropharmacology, 2024)
Chronic postoperative pain (CPSP) is a major issue after surgery, which may impact on patient’s quality of life. Traditionally, CPSP is believed to rely on maladaptive hyperalgesia and risk factors have been identified that predispose to CPSP, including acute postoperative pain. Despite new models of prediction are emerging, acute pain is still a modifiable factor that can be challenged with perioperative analgesic strategies. In this review we present the issue of CPSP, focusing on molecular mechanism underlying the development of acute and chronic hyperalgesia. Also, we focus on how perioperative strategies can impact directly or indirectly (by reducing postoperative pain intensity) on the development of CPSP.
Keywords: regional anesthesia